SENGKETA PERBATASAN WILAYAH KASHMIR DALAM PERSPEKTIF HUKUM INTERNASIONAL - Riadhi Alhayyan; Arif Arif; Jelly Leviza (Journal of USU International Law, 2013)
ABSTRACT Riadhi Alhayyan 090200029 Kashmir border dispute was very influential and disturbing in the South Asia region, because the dispute involves two major states of India and Pakistan. The bickering two countries fighting over kashmir region as the territory continues and has attracted a lot of attention from various countries in the settlement of the dispute. Kashmir border dispute has put a serious challenge for analysts and policy makers because the conflict is complex and heterogeneous. Kashmir, the disputed territory that lies at the foot of the Himalayas, under the rule of the three countries. Jammu-Cash Society ¬ hmir entered Indian territory, while the people of Ladakh and Jammu-Kashmir-Pakistan respectively controlled by China and Pakistan. Among the three, only the Jammu-Kashmir's turbulent and demanding independence. The research method with normative legal research or legal research literature conducted by examining the literature material, and empirical legal research. The study used the law is normative legal research or collectively, the literature study (library research) with the acquisition of secondary data sourced cider magazines, books, journals, newspapers, online websites, and other library documents. Analysis of the data used is qualitative analysis, ie data obtained and subsequently systematically compiled and then analyzed qualitatively in order to achieve clarity issues to be discussed and the results are set forth in the form of a thesis. Based on the results of the study authors that the status area Kashmir under international law is in dispute, as India and Pakistan both claim Kashmir as their territory. But the ruler of Kashmir when it was a Hindu, would prefer to join with India, so that Kashmiris are now split into two, Pakistan and Kashmir Kashmir India. Kashmir struggle in a dilemma. If using peaceful means and approach to politics, India claimed that the people of Kashmir have accepted the status quo, to be a part of India. Kashmir territorial dispute and the Kashmir conflict occurs because of a conflict of interest between the two countries and the political power that is manifested through unilateral claims of India and Pakistan. Including religious factor, pakistan claims that the khasmir is a muslim majority area integral for pakistan while also claiming in kashmir hindu community are integrated with india. Factors as well as border, it is located in the teritory of Kashmir Indian authorities, however, a dispute can not be separated from the colonial regime that tends to make the inter-state border artificially, meanings the colonial regime tends to create a new border regime without notice in the interests of natural factors such as ethnicity,and socio-cultural condition. Solution to solve the Kashmir region between India struggle with Pakistan should be implemented bilateral relations between the two countries. UN and SAARCsebaiknya entitles India and Pakistan over the Kashmir region in accordance with the location of each region. So there is no reason for India and Pakistan to fight each other for control of the Kashmir region as a whole. In addition, the United Nations and the SAARC should be decisive in resolving the Kashmir conflict annexation. For countries that do not abide by the decision of the United Nations and the SAARC should be subject to strict law. . Keywords: Kashmir dispute